Aerobic bacteriology of chronic suppurative otitis media: a hospital based study - Nazir, Asifa; Kadri, S. M. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic suppurative otitis media (CSOM) remains one of the most common childhood chronic infectious diseases worldwide, affecting diverse racial and cultural groups both in developing and industrialized countries. It involves considerable morbidity and can cause extra- and intra-cranial complications. The aim of this study was to determine the microbial diversity and the antibiogram of aerobic bacterial isolates among patients suffering from CSOM who attended the ENT Department of SMHS hospital, a tertiary care centre located in the heart of the Kashmir valley. Methods: A total of 154 patients clinically diagnosed with CSOM were enrolled in the study and the samples were obtained from each patient using sterile cotton swabs and cultured for microbial flora. Drug susceptibility testing for aerobic isolates was conducted using Kirby-Bauer disc diffusion method. Results: Out of total 154 ear swabs processed, microbial growth was seen in 138 (89.61%) while 16 (10.38%) samples showed no growth. In 102 (66.23%) samples mono-microbial growth was seen whereas 26 (16.88%) samples showed poly-microbial growth. The most frequent organism isolated was Pseudomonas aeroginsa followed by Staphylococcus aureus and Proteus sp. The most effective antibiotic against Pseudomonas aeroginsa was amikacin followed by imipenem and piperacillin plus tazobactam, while as Staphylococcus aureus showed maximum sensitivity to vancomycin. Conclusion: Otitis media linked with high levels of multiple antibiotic resistant bacteria is a major health concern in all age groups of the study population. An appropriate knowledge of the etiology and antibacterial susceptibility of microorganisms would contribute to a rational antibiotic use and the success of treatment for chronic supportive otitis media.